Detailed analysis of c-di-GMP mediated regulation of csgD expression in Salmonella typhimurium - Ahmad, Irfan (BMC Microbiol, 2017)
BACKGROUND: The secondary messenger cyclic di-GMP promotes biofilm formation by up regulating the expression of csgD, encoding the major regulator of rdar biofilm formation in Salmonella typhimurium. The GGDEF/EAL domain proteins regulate the c-di-GMP turnover. There are twenty- two GGDEF/EAL domain proteins in the genome of S. typhimurium. In this study, we dissect the role of individual GGDEF/EAL proteins for csgD expression and rdar biofilm development. RESULTS: Among twelve GGDEF domains, two proteins upregulate and among fifteen EAL domains, four proteins down regulate csgD expression. We identified two additional GGDEF proteins required to promote optimal csgD expression. With the exception of the EAL domain of STM1703, solely, diguanylate cyclase and phosphodiesterase activities are required to regulate csgD mediated rdar biofilm formation. Identification of corresponding phosphodiesterases and diguanylate cyclases interacting in the csgD regulatory network indicates various levels of regulation by c-di-GMP. The phosphodiesterase STM1703 represses transcription of csgD via a distinct promoter upstream region. CONCLUSION: The enzymatic activity and the protein scaffold of GGDEF/EAL domain proteins regulate csgD expression. Thereby, c-di-GMP adjusts csgD expression at multiple levels presumably using a multitude of input signals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-017-0934-5) contains supplementary material, which is available to authorized users.